THE ROLE OF PUBLIC RELATIONS MANAGEMENT IN BUILDING THE REPUTATION OF EDUCATIONAL INSTITUTIONS IN THE DIGITAL ERA (CASE STUDY AT ULUL ALBAB ISLAMIC EDUCATIONAL INSTITUTION) - Fansori, Rosihan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the rapidly developing digital era, the role of public relations in educational institutions has become very strategic, especially in building and maintaining a positive reputation on an ongoing basis. This research focuses on the role of public relations management at the Ulul Albab Islamic Education Foundation in building a positive image in the digital era. As an educational institution based on Islamic values, this foundation is responsible for producing a generation with knowledge and morals, while maintaining good relations with stakeholders such as students, parents, alumni and the community. This research uses a qualitative approach with a case study method to analyze the strategies, challenges and effectiveness of public relations programs in conveying positive messages and strengthening public trust. The research results show that effective public relations management can introduce the foundation's superior programs and values through appropriate communication, while managing the challenges of the digital era such as the flow of information on social media which quickly influences public opinion. By utilizing technology and digital communication strategies, public relations is expected to be able to expand the reach of communication, improve the positive image of the foundation, and create better relationships with various parties. This research provides an overview of the strategic steps that have been taken by the Ulul Albab Islamic Education Foundation to maintain its reputation amidst the changing dynamics of digital communication.